Isolated T Wave Inversion in Lead aVL: An ECG Survey and a Case Report - Hassen, Getaw Worku; Costea, Ana; Carrazco, Claire; Frew, Tsion; Swaminathan, Anand; Feliberti, Jason; Chirurgi, Roger; Smith, Tennyson; Chen, Alice; Thompson, Sarah; Gushway-Henry, Neola; Simmons, Bonnie; et al. (Emergency Medicine International, 2015)
Background. Computerized electrocardiogram (ECG) analysis has been of tremendous help for noncardiologists, but can we rely on it? The importance of ST depression and T wave inversions in lead aVL has not been emphasized and not well recognized across all specialties. Objective. This study’s goal was to analyze if there is a discrepancy of interpretation by physicians from different specialties and a computer-generated ECG reading in regard to a TWI in lead aVL. Methods. In this multidisciplinary prospective study, a single ECG with isolated TWI in lead aVL that was interpreted by the computer as normal was given to all participants to interpret in writing. The readings by all physicians were compared by level of education and by specialty to one another and to the computer interpretation. Results. A total of 191 physicians participated in the study. Of the 191 physicians 48 (25.1%) identified and 143 (74.9%) did not identify the isolated TWI in lead aVL. Conclusion. Our study demonstrated that 74.9% did not recognize the abnormality. New and subtle ECG findings should be emphasized in their training so as not to miss significant findings that could cause morbidity and mortality.